Workload Analysis to Determine Labor Requirements Using the Workload Analysis (WLA) Method - Ferdian Nizar Afnan Fairuz; Handy Febri Satoto (Telkom University, 2026)
UD. Hardi Jaya is a shoe manufacturing enterprise implementing a job order production system, causing fluctuating production demand and workload imbalances across production sections. This study aims to analyze workload and determine optimal workforce requirements using the Work Load Analysis (WLA) method. Data were collected through observation, interviews, documentation, and stopwatch time study involving 15 production operators in the cutting, sewing, manual work, sole installation, and packing sections. Data were analyzed using data uniformity and adequacy tests before calculating cycle time, normal time, standard time, and workload values. The results indicate that several operators experienced overload conditions with workload values above 100%, including Sole Installation 1 (114.54%), Sole Installation 2 (109.52%), Cutting 1 (102.85%), and Manual Work operators. The sole installation section was identified as the main production bottleneck with an output capacity of only 68 pairs per day, which was below the production target of 102 pairs per day. Based on WLA calculations, the ideal workforce requirement was 19 workers to achieve the production target of 3,067 pairs per month, compared with the current workforce of 15 workers. However, considering production capacity and labor cost factors, maintaining the existing workforce with an overtime system was considered more economical than recruiting additional workers. The WLA method can support workforce planning, workload balancing, and improved production efficiency.